(untitled) (American Journal of Islam and Society, 2003)
How should societies that have transitioned from authoritarian to democratic rule deal with the atrocities and gross human rights violations of their immediate past? Should those implicated in the crimes of past regimes be prosecuted? This sophisticated volume attempts to address such questions. About one-third of the book is comprised of well-reasoned theoretical chapters that answer the above questions by creating a space in liberal justice for forgiveness. The remainder consists of empirical contributions that describe the ways in which international institutions and five countries (Chile, Guatemala, South Africa, Rwanda, and Northern Ireland) have responded to such crimes. Unlike the theoretical section, most contributions here argue that while memory and forgiveness (the truth commissions) are important, they are not enough to meet the victims’ psychological needs and do not guarantee non-repetition. The introduction rightly acknowledges that some of the chapters argue in different directions. Doing justice in the aftermath of civil conflict is a thorny problem. In liberalism, criminal justice always has been straightforward: the courts, the mouthpiece of objective law, have to mediate and impose punishment if the perpetrator is proven guilty. Punishment must consist of penalties that annul the advantages seized by the criminal, compensate the victim in the case of ...